1977
DOI: 10.1042/bj1610535
|View full text |Cite
|
Sign up to set email alerts
|

A latent form of collagenase in the involuting rat uterus and its activation by a serine proteinase

Abstract: 1. The involuting rat uterus displays an extremely rapid breakdown of collagen. Collagenase activity can be assayed directly in the insoluble 6000g pellet of uterine homogenates. At 1 day post partum, about 85% of this collagenase activity is in a latent form. 2. This latent form can be activated by trypsin or by a serine proteinase present in the uterine pellets. 3. The activating enzyme of the tissue is inhibited by a wide spectrum of trypsin inhibitors, including Trasylol, soya-bean and lima-bean trypsin in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
1

Year Published

1979
1979
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 28 publications
4
39
1
Order By: Relevance
“…Also, it is not easy to determine if the activation process is due to the destruction of a bound endogenous collagenase inhibitor or to the cleavage of a zymogen form to yield an active enzyme. Although, most authors supported the latter explanation, the structural basis for collagen-degrading specificity is not clearly understood (Woessner, 1977). The most commonly used activator of collagaenase is arguably 4-Aminophenylmercuric Acetate (APMA).…”
Section: Factors Affecting Collagenase Activitymentioning
confidence: 92%
See 1 more Smart Citation
“…Also, it is not easy to determine if the activation process is due to the destruction of a bound endogenous collagenase inhibitor or to the cleavage of a zymogen form to yield an active enzyme. Although, most authors supported the latter explanation, the structural basis for collagen-degrading specificity is not clearly understood (Woessner, 1977). The most commonly used activator of collagaenase is arguably 4-Aminophenylmercuric Acetate (APMA).…”
Section: Factors Affecting Collagenase Activitymentioning
confidence: 92%
“…Sakamoto et al (1972) suggested that trypsin (another common activator) might be used to bind trypsin inhibitors such as α 2 -macroglobulin, thereby preventing these from inhibiting collagenase. Woessner (1977) found that trypsin enhanced collagenase activity by almost 30%. α 2 -macroglobulin is able to inactivate an enormous variety of proteinases (including serine-, cysteine-, asparticand metalloproteinases).…”
Section: Factors Affecting Collagenase Activitymentioning
confidence: 99%
“…Treatment with 3 M NaSCN, that destroys complexes of ccz-macroglobulin in other systems [21], did not reveal collagenase activity in supernatants and extraction of the fibrous material of tumor homogenates with 5 M urea and ammonium sulfate precipitation was necessary to detect any collagenase, suggesting a high affinity of collagenase for its substrate. As for collagenase in extracts of other tissues [5,27], part of the total activity was latent and its activation was closely similar as it could be activated by trypsin, by prolonged storage at -20 "C or by preincubation at 37 'C without trypsin, causing an apparent autoactivation.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested that besides trypsin, unidentified factors are capable of activating latent collagenase in crude tumor extracts. Since neutral proteases other than trypsin have been previously described to activate latent collagenase in vivo [5] and in vitro [20], we had tried to inhibit proteolytic activity in tumor extracts. Of the inhibitors added to the urea extract under the conditions used to prepare crude collagenase, only inhibitors known to block serine protcases caused complete inhibition (Table 2).…”
Section: C'ollagenase In Tumor Exrrucismentioning
confidence: 99%
See 1 more Smart Citation